MANAJEMEN MUTU DI DALAM LEMBAGA PENDIDIKAN - Arasyid Mahani, Muhniansyah (Al-Manba, 2023)
Quality is a measure of the good and bad of an object, condition, level, or degree (smartness, intelligence, and so on). Failure in the quality of education can be seen from two forms of failure, namely general and specific. From a general perspective, the causes of system failure include weak curriculum design, buildings that do not meet the requirements, poor work environment, inappropriate work systems and procedures, haphazard work schedules, insufficient resources, and inadequate staff development. adequate. From a special form the cause of failure is a rule that is not followed or obeyed. It could also be members' lack of knowledge and skills, lack of motivation, communication failures and problems with educational equipment. Solutions to overcome educational quality failures or improve them are the key tasks of an education manager (school principal) in an educational institution